A feasibility study to assess the design of a multicentre randomized controlled trial of the clinical and cost- effectiveness of a caregiving intervention for people following hip fracture surgery. (2021) - Smith, T.; Clark, L.; Khoury, R.; Man, M- S.; Hanson, S.; Welsh, A.; Clark, A.; Hopewell, S.; Pfeiffer, K.; Logan, P.; Crotty, M.; Costa, M.; et al.
No abstract available